Integrated Marketing Communications in web 2.0 environment: Challenges and Opportunities of online presence - Abashidze, Irakli (Journal of Research in Marketing (ISSN: 2292-9355), 2017)
In today’s digital world, it is impossible to achieve wide scale marketing goals without using modern methodology of integrated marketing communications management. Companies experience increasing influence of consumer-generated content and online reviews. Therefore, the need for specific tools and methodology of integrated marketing communications management increases in parallel with expanding Web 2.0 community. The features of Web 2.0 environment eliminate effectiveness of “traditional” marketing methods and creates the need for implementing modern approaches. However, the gap between “traditional” and “modern” marketing has faded away. Today, integrated marketing communications management is a complex and ubiquitous array of activities. The process of integrated marketing communications management in Web 2.0 environment contains challenges, alongside with numerous opportunities. The paper aims at identifying risks, threats, opportunities and reviews management methodology of integrated marketing communications in Web 2.0 environment. The introduction represents general overview of the issue, followed by literature review, discussion and conclusion. The main goal of the author is to present personal vision of the issue through own observation and literature study.